2005
DOI: 10.7863/jum.2005.24.7.1031
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Diagnosis of a Tracheal Extramedullary Plasmacytoma

Abstract: olitary extramedullary plasmacytoma (EMP) is a rare tumor constituting 4% of all plasma cell neoplasms. It may occur in any reticuloendothelial system containing organs but is found most frequently in the head and neck regions, which are rich in lymphoid tissue. The most common sites of origin are the subepithelial tissues of mucous membranes of the oronasopharynx and paranasal sinuses. [1][2][3][4][5] Sonography has no role in the evaluation of tracheal lesions. We report a case of tracheal plasmacytoma that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…Once disease becomes multiple myeloma, then prognosis is not as good as plasmacytoma; chemotherapy should be added [13,14] . The potential for malignant systemic progression is higher for solitary plasmocytomas of bone than for extramedullary plasmocytomas [15] . It has been reported that extramedullary localizations of myeloma originating from the cranial bone are usually responding well to new drugs (e.g., thalidomide, bortezomib, and lenalidomide) compared to CNS myeloma [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Once disease becomes multiple myeloma, then prognosis is not as good as plasmacytoma; chemotherapy should be added [13,14] . The potential for malignant systemic progression is higher for solitary plasmocytomas of bone than for extramedullary plasmocytomas [15] . It has been reported that extramedullary localizations of myeloma originating from the cranial bone are usually responding well to new drugs (e.g., thalidomide, bortezomib, and lenalidomide) compared to CNS myeloma [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Rarely extramedullary plasmacytoma can occur in the thyroid, hypopharynx, larynx, parotid gland, cervical lymph nodes and middle ear. Other areas affected include gastrointestinal tract, bladder, breast, central nervous system, testis, skin, lung parenchyma and bronchus [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…Extramedullary plasmacytoma respond well to radiation therapy [2,6,13]. Data from literature shows that around 60 % of patients with plasmacytoma of upper aerodigestive tract had no recurrence or progression to multiple myeloma whereas 22 % cases had recurrence and 16 % showed progression to multiple myeloma [2,3,14]. Therefore even though the prognosis of plasmacytoma is better than that of multiple myeloma, a long term follow up is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Less common still are tracheal tumors, which account for only 1-2% of all respiratory tract tumors (5,6) , affecting mainly the lower third of the tract (7) . Such tumors can be locally invasive (3) , adenoid cystic carcinoma and squamous cell carcinoma being the malignant tumors most often affecting the trachea (5,6,8) . The most common symptoms are related to airway obstruction, dyspnea being the most common, and become more evident when the tracheal lumen is narrowed by more than 75% (5,9) .…”
mentioning
confidence: 99%
“…Extramedullary plasmacytoma of the trachea is a rare plasma cell malignancy (accounting for only 4% of plasma cell tumors), having been described in soft tissues outside the bone marrow, involving the submucosal lymphoid tissue, and occurring at different locations, especially in the upper airways, most often in the paranasal sinuses or nose (5,8,10) . Involvement of the larynx, hypopharynx, cervical glands, esophagus, cervical lymph nodes, middle ear, and mastoid is rare (5) , and tracheal involvement is even rarer (5,11-13) , occurring in only 3% of all extramedullary plasmacytomas (9) .…”
mentioning
confidence: 99%